Analisis Literatur: Implikasi Sosial dan Keselamatan Kerja dari Penggunaan Grass Cutter Ergonomis di Perkebunan Sawit - Arief Panca Putra; Bagus Nugroho; Subakho Aryo Saloko (Journal of Humanities, Social Sciences, and Education, 2025)
The use of grass cutters in oil palm plantations is a crucial activity in weed control, which can impact land productivity and worker well-being. However, the use of non-ergonomic tools carries the risk of health problems such as musculoskeletal injuries, excessive fatigue, and decreased work efficiency. This literature analysis aims to explore the social and occupational safety implications of implementing ergonomic grass cutter designs in oil palm plantations. The method used is a literature review of national and international journals published between 2015 and 2024, focusing on ergonomics, occupational health, and socioeconomic impacts in the plantation sector. The analysis results indicate that the use of ergonomic grass cutters can improve work comfort, reduce the risk of injury, and increase worker productivity. In addition, improved tool design also has a positive impact on social relations between workers, reducing absenteeism, and increasing income due to more optimal work results. The main challenges identified are limited access to ergonomic tools, lack of training, and relatively high initial investment costs. This study recommends the need for policy interventions and training support for workers to optimize the benefits of ergonomic grass cutters. In conclusion, the application of ergonomic technology in oil palm plantations is not only relevant for occupational safety but also contributes to social sustainability and worker well-being.